Valuing rural hospitals - the Australian experience - Alan Chater; Samuel Webster (James Cook University, 2023)
Introduction: Over many years in Australia, public hospitals were funded on historical grounds with about 40% of running costs provided by the national government. In 2010, a national reform agreement established the Independent Hospital Pricing Authority (IHPA) to put in place activity-based funding, where the national government contribution was based on activity and National Weighted Activity Units (NWAU) and a National Efficient Price (NEP). Rural hospitals were exempted from this on the assumption that they were less efficient and activity more variable.Method: IHPA developed a robust system of data collection for all hospitals including rural hospitals. Initially this was based on historic data but with increasing sophistication of data collection, a predictive model was developed that is termed the National Efficient Cost (NEC).Results: The cost of hospital care was analyzed. The very smallest hospitals that saw fewer than 188 standardized patient equivalents (NWAU) per year were excluded as there were very few very remote hospitals with justified variation in their costs. A number of models were tested for their predictive value. The selected model successfully balances simplicity, policy considerations, and predictive power. The selected model combines an activity-based payment with a flag fall:Low volume (less than 188 NWAU) are paid a set amount of A$2.2M;Those between 188 and 3500 NWAU are paid a diminishing flag fall + activity payment; andThose above 3500 NWAU are paid on activity alone (same as larger hospitals)Discussion: The last 10 years has seen an increasing sophistication in measurement of hospital costs and activity allowing a deeper understanding of these aspects. The funding of hospitals by the national government is still distributed by the states but there is now as a greater transparency of cost, activity and efficiency. The presentation will highlight this and consider the implication and possible next steps.